Glokalność w globalnej sieci. Analiza zjawiska sieciowej tożsamości narodowej na przykładzie RuNetu - Drewniak, Anna (Człowiek i Społeczeństwo, 2015)
The aim of the text is to use the concept of glocality (Robertson) to discuss the specific character of RuNet, the Russian-language Internet, the limits of which are not based on geographical boundaries but language. The emergence of RuNet, both at the level of nomenclature and at the level of giving it peculiar characteristics that distinguish it from the rest of the web resources, is related to the initial lack of compatibility of the Cyrillic and Latin Internet. On the one hand, due to the emergence of a separate Russian-language space on the web, the native search engines (such as Яндекс), blogging platforms or social networking sites (ВКонтакте) preferred by the Russians occupy several or sometimes even a dozen or so percent of the world market. This is an obvious phenomenon as the portals of a group of German-speaking, French-speaking, Latin American countries and China do not achieve such results. On the other hand, the difference in notation has favoured self-isolation of RuNet, which, by its distinctiveness, has become a part of the web isolated on a global scale. One of the most significant indicators of RuNet’s glocality is its functioning in the field of neo-imperial ideas. The notion which is visible on every level of the decentralized message that Russia is once again becoming an empire is a constantly recurring chorus of Internet divagations. The glocality of the Russian-speaking Internet does not constitute the plain total sum of pre-national and postnational elements, but the ratio of these two systems, a peculiar, original version of the “third way.” The summing up of the article will be an attempt at answering the question where this way will lead RuNet.